Peran Mahasiswa KKN Universitas Karimun dalam Mengedukasi Kesehatan Anak melalui Sosialisasi Mencuci Tangan dan Kebersihan Gigi (Lembaga Pengembangan Kinerja Dosen, 2025)
Maintaining health is important for every individual, because by maintaining health, it can prevent susceptibility to disease. One important effort to get used to is maintaining hand and mouth hygiene. Washing hands with soap is the process of removing dirt and dust from both hands using water and soap, which can prevent various diseases such as diarrhea and ARI. While brushing teeth is the process of cleaning teeth from food residue stuck in the teeth and oral cavity, the benefit of getting used to brushing teeth is to prevent tooth decay. The importance of awareness about personal hygiene must be instilled from an early age, starting from this, KKN University Karimun students, and then conducted socialization activities at State Elementary School 004 and State Elementary School 007, Belat District. This socialization activity used simple lecture methods, direct practice, educational games, and audio-visual media. From the results of the socialization activities that have been carried out, it has been successful in providing an understanding of the importance of maintaining personal hygiene through washing hands and brushing teeth. With the education that has been provided, it is hoped that it can have a positive impact on student behavior in maintaining personal hygiene.